Psychological factors of student’s social activity - Anastasiia Bazilenko; Nataliia Barna; Olga Lytvynenko (Social Welfare: Interdisciplinary Approach, 2019)
This article describes the structure of psychological factors influencing students’ social activity and empirical results of its research. The psychological factors that promote the development of social activity and those that inhibit it have been characterized. The personal favorable factors of social activity include: students’ psychological attitudes towards the value of social activity; feeling like a full member of the student group; positive personal experience; formed social abilities; the desire for self-realization, self-knowledge, self-creation, self-regulation; sense of personal value; awareness of the positive resources available and opportunities for their actualization; self-belief; self-promotion; comprehensive ideas about social activity and its factors; ability to take initiative in the social sphere; ability to self-regulate. The factors that slow down students’ social activity are: wrong profession, despair in others, despair in social ideals, attitudes that make a person inflexible to changing conditions, absence or weakened sense of social responsibility.